Meta-Analysis of the Factors Influencing the Restoration of Spontaneous Circulation After Cardiopulmonary Resuscitation - An, Hui-Ru; Han, Yi-Ran; Wang, Tian-Hao; Chi, Fei; Meng, Yu; Zhang, Chun-Yan; Liang, Jian-Qin; Li, Xiang-Lan (Frontiers in Physiology, 2022)
Objective This study aimed to systematically evaluate the factors influencing the restoration of spontaneous circulation (ROSC) after cardiopulmonary arrest (CA). Methods Relevant papers on the factors influencing the ROSC in patients with CA were retrieved from PubMed, Embase, Cochrane Library, China Biology Medicine disk, China National Knowledge Infrastructure, Wanfang, and VIP databases. After screening, data extraction, and quality evaluation of the papers, a meta-analysis was carried out. Results A total of 36 papers, involving a total sample size of 2,305 cases, were included. The meta-analysis revealed that the location and time of onset of CA, the type of cardiac rhythm at first monitoring, the start time of cardiopulmonary resuscitation (CPR), the use of electric defibrillation, and the cumulative dose of adrenaline all significantly impacted the ROSC (p < 0.05) and may have affected its success rate. The pH value at CA onset, combined use of adrenaline and vasopressin, CPR duration, mechanical cardiac compression use, and whether CA was caused by heart disease had no significant effect on ROSC. Conclusion The location and time of onset of CA, the cardiac rhythm at first monitoring, the start time of CPR, the use of electric defibrillation, and the cumulative dose of adrenaline significantly impacted the ROSC.